Risk factors for tuberculosis and diabetes mellitus comorbidity in West Sumatra, Indonesia: A matched case-control study - Irwan Ashari; Agung Sutriyawan; Witri Dewi Mentari; Haidir Syafrullah; Meda Yuliani; Erika Dewi Noorratri (Journal of Public Health and Development, 2026)
The comorbidity between tuberculosis (TB) and diabetes mellitus (DM) (TB-DM) is a growing public health issue globally. Patients with TB-DM tend to experience more severe disease, including an increased risk of death, treatment failure, and pulmonary complications. This study aims to analyse the sociodemographic, clinical, and environmental risk factors that influence the prevalence of TB-DM comorbidity in West Sumatra Province. This study used a matched case-control study design. The population in this study consisted of TB-DM patients recorded in 2024. The study sample consisted of 830 people in the case group (TB-DM) and 830 people in the control group (TB). The sampling technique used was total sampling. Statistical tests used the McNemar test and Conditional Logistic Regression. Significant risk factors for tuberculosis and diabetes mellitus (TB-DM) comorbidity are age (OR = 11.500; 95% CI: 8.39–15.76, p = 0.0001), occupation (OR = 1.559; 95% CI: 1.201–2.022, p = 0.0001), pulmonary tuberculosis (OR = 6.615; 95% CI: 3.692–11.853, p = 0.0001), and history of TB treatment, with patients who had a history of relapse being at higher risk (OR = 2.857; 95% CI: 1.857–4.393, p = 0.0001). Meanwhile, residential area and referral status did not show significant differences, with ORs of 1.218 (95% CI: 0.852–1.740, p = 0.277) and 1.246 (95% CI: 0.899–1.727, p = 0.185), respectively. In the final model, age (OR = 11.031; 95% CI: 8.014–15.185) and type of tuberculosis (OR = 4.895; 95% CI: 2.327–10.296) remained significant as risk factors for TB-DM comorbidity. Age, occupation, type of tuberculosis, and history of TB treatment are significantly associated with tuberculosis and diabetes mellitus (TB-DM) comorbidity. It is important to conduct early screening for diabetes in TB patients and to manage both diseases simultaneously to improve treatment outcomes and reduce morbidity and mortality.